1973
DOI: 10.1038/hdy.1973.78
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mating and artificial selection

Abstract: SUMMARYTheory is developed to assess the consequences of assortative mating immediately following truncation selection.Truncation selection is expected to generate negative correlations between homologous genes and between non-homologous genes in the same and different gametes. Truncation selection is expected to reduce the maximum marital correlation that can be realised by assortative mating based on phenotypic resemblance within a selected population.It is concluded that assortative mating among selected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
2

Year Published

1975
1975
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
0
13
2
Order By: Relevance
“…In this study, the redistribution of test resources among families by varying their sizes under fixed total test resources magnified the effect of PAM, which by itself provides a large enhancement of V A(BP) , particularly under low-selection-intensity scenarios (Baker 1973;De Lange 1974;Jorjani 1995;. The enhancement of V A(BP) observed in this study exceeds the magnitude reported earlier under unbalanced mating schemes Lstibů rek et al 2004).…”
Section: Resultscontrasting
confidence: 49%
“…In this study, the redistribution of test resources among families by varying their sizes under fixed total test resources magnified the effect of PAM, which by itself provides a large enhancement of V A(BP) , particularly under low-selection-intensity scenarios (Baker 1973;De Lange 1974;Jorjani 1995;. The enhancement of V A(BP) observed in this study exceeds the magnitude reported earlier under unbalanced mating schemes Lstibů rek et al 2004).…”
Section: Resultscontrasting
confidence: 49%
“…This allows the depiction of genotypes as normal random variables. BAKER (1973) used normal approximations and presented results as a function of loci number. Our analysis differs from that of BAKER in that results are not presented as a function of loci number.…”
Section: A Assumptionsmentioning
confidence: 99%
“…In a simulation study, D E L ANGE (1974) concluded that assortative mating is most useful when the trait is polygenic, selection intensity is low and heritability (h l ) high. BAKER (1973) studied the effectiveness of assortative mating of selected parents followed by selection of offspring and claimed that in most cases assortative mating will increase selection response in the progeny but by no more than 10 p. 100. When the fraction of parents selected is 20 p. 100 or less, BAKER found that assortative mating will increase selection response by no more than 4 or 5 p. 100.…”
Section: Introductionmentioning
confidence: 99%